Clinical pharmacy, pharmaceutical care: Concepts, philosophy, professional practice and its application to the Colombian context (2012)
ABSTRACT: Pharmaceutical care is a healthcare practice that has been implemented recently worldwide. Its aim is the rational medication use and the achievement of desired therapeutic goals that improve the patient quality of life. This review see ks to define and relate the terms: pharmaceutical care, clinical pharmacy and pharmacotherapy follow-up, which are misunderstood in our field. Likewise, it seeks to show the transformation that has had this practice, from the traditional pharmacist (limited to the production and distribution of medicines) into the comprehensive pharmacist nowadays (active participant of interdisciplinary health teams and responsible for all the medication needs at a political, social and economic level). An approach of these terms to the National Health System context is also the goal of this review. Through this, it is intended to homologate the terminology of this practice in our country and to state future reflections and challenges that pharmacists and different entities will have to adopt, enabling this professional practice to achieve the desired therapeutic goals settled by the health team, thus improving the patient quality of life.